Donald Trump in historical perspective : dead precedents - Harvey, Michael, 1960- (New York, NY : Routledge, 2022)
"Donald Trump in Historical Perspective: Dead Precedents is a collection of essays that utilizes the thinking of historians, philosophers, and political scientists to explore historical parallels to the presidency of Donald J. Trump, the 45th President of the United States of America"--
Keywords: Trump, Donald, -- 1946-; Trump, Donald, -- 1946- -- Influence; Political leadership -- United States; United States -- Politics and government -- 2017-2021.; PSYCHOLOGY / Applied Psychology; BUSINESS & ECONOMICS / Leadership; BIOGRAPHY & AUTOBIOGRAPHY / Presidents & Heads of State